Difusi Produk Intermediate Baru Very Few Layers Graphene (VFLG) dan Produk Turunannya oleh Inkubator Bisnis Graphene Guard - Amri, Amun; Yenti, Silvia Reni; Heltina, Desi; Herman, Syamsu; Aziz, Azridjal; Nadhifah, Evi; Ekwarso, Hendro (Journal of Community Engagement Research for Sustainability, 2022)
Product diffusion of very few layers of graphene (VFLG) and its derivative (car/motorcycle polish) has been carried out by the Graphene Guard business incubator. The steps and strategies began with discussions in a discussion group forum (FGD) inviting experts in order to find the best marketing patterns. In this case the Canvas method was chosen as a marketing strategy. As a follow-up to the results of the FGD, several activities were carried out. Improvements to the system and production capacity were carried out by adding production equipment, innovating production systems and creating production automation systems. The next step was to design brand and logo activities as well as product labels. The design and manufacture of online and offline sales systems were carried out to follow up on increasing production capacity. To increase the effectiveness of marketing, promotional activities were carried out in the form of advertising, creating brochures, production videos and participating in exhibitions. The results obtained indicated that the marketing of the new intermediate product, very few layer graphene (VFLG) and its derivative products in the form of car polishes, was still experiencing diffusion problems, as evidenced by the low sales capacity. This was realized because this product was a new product and was not yet known to the public. Especially for VFLG products, the additional obstacle was that this product was an intermediate product, thus only certain groups of people need it. Evaluation steps are needed for continuous improvement in order to continue to strengthen the diffusion of this product in society.